Low-temperature sintering of Ti1−xCux/3Nb2x/3O2 (x = 0.23) microwave dielectric ceramics with CuO and B2O3 addition. Issue 3 (15th February 2018) - Shao, Hui; Liu, Zhifu; Jian, Gang; Li, Yongxiang
Abstract: The influence of CuO and B2 O3 addition on the sintering behavior, microstructure and microwave dielectric properties of Ti1−x Cux/3 Nb2x/3 O2 (TCN, x = 0.23) ceramic have been investigated. It was found that the addition of CuO and B2 O3 successfully reduced the sintering temperature of TCN ceramics from 950 to 875 °C. X-ray diffraction studies showed that addition of CuO-B2 O3 has no effect on the phase composition. The TCN ceramics with 0.5 wt% CuO-B2 O3 addition showed a high dielectric constant of 95.63, τ f value of + 329 ppm/°C and a good Q × f value of 8700 GHz after sintered at 875 °C for 5 h, cofirable with silver electrode.